(untitled) (Comprehensive Journal of Science, 2025)
This study designs an off-grid solar and battery-powered solar energy system for a hypothetical home in Libya. A stand-alone solar energy system was proposed as a means of supplying this home with electricity throughout the day. Meteorological data for a hypothetical location was examined to gather additional facts. This study includes a detailed discussion of the main components of this system: batteries, charge controllers, inverters, and solar panels. Calculations were performed to determine the home’s electrical load and the amount of solar radiation present. Data from this system was measured and analyzed using PVSyst software. In terms of scale and design, this study supports the operation of an integrated off-grid home in the Libyan desert, so the same procedures used in this research can be used in other locations to benefit from these findings.